A Combined Localization and Geographic Routing Algorithm for Rapidly-Deployed Wireless Sensor Networks. (2008) - Qu Qu, Hui Hui; Wicker Wicker, Stephen B. Stephen B.
Abstract : We consider a network of randomly-deployed, low-cost sensors and a single powerful sink node. A partition-based localization algorithm is proposed in which the sink node imparts sector-based location information through the phased-array transmission of a series of beacons. One-hop neighbor information is used by each sensor in a series of sector-partitioning routines to identify the sub-sector in which it resides. A geographic routing algorithm is then proposed which uses the sector-based localization results as the basis for a routing algorithm. Simulation results indicate that the performance of our localization algorithm improves with node density, and that the performance of the combined localization and routing algorithm in the presence of severe measurement noise is comparable with that provided by the same routing algorithm using perfect location information.